The impact of financialisation on the wage share: a theoretical clarification and empirical test - Post-Keynesian Economics Study Group; Köhler, Karsten; Guschanski, Alexander; Stockhammer, Engelbert (Durham, 2018)
"It is frequently asserted that financialisation has contributed to the decline in the wage share. This paper provides a theoretical clarification and a systematic empirical investigation. We identify four channels through which financialisation can affect the wage share: (1) enhanced exit options of firms; (2) rising price mark-ups due to financial overhead costs for businesses; (3) increased competition on capital markets and shareholder value orientation; and (4) the role of household debt in increasing workers’ financial vulnerability and undermining their class consciousness. The paper compiles a comprehensive set of empirical measures of financialisation and uses it to test these hypotheses with a panel regression of 14 OECD countries over the 1992-2014 period. We find strong evidence for negative effects of financial liberalisation and financial payments of non-financial corporations on the wage share that are in the same order of magnitude as the effects of globalisation."